Precambrian Ultramfic Rocks South of Sermilik, Frederikshåb District, South-West Greenland. - Mísař, Zdeněk (Meddelelser om Grønland, 1973)
The petrography and both whole rock and trace element chemistry of ultramafic bodies is described. The ultramafic bodies occur in large numbers in the Precambrian south of Sermilik and are associated with amphibolites. Their shapes are secondary, but in many cases the arrangement of both small lenses and major bodies suggests that they had a primary sheet-like form. The original contacts of the ultramafic rocks with the country rocks have not been preserved because they developed reaction zones with their host rocks during metamorphism under amphibolite facies conditions. The ultramafics have been divided into three main groups. The first group consists of primary serpentinized peridotites and serpentinites, which escaped amphibolization and form the cores of the bodies. The second group includes amphibolized primary ultramafics such as foliated tremolite/actinolite-bearing rocks, which formed at the outer part of the ultramafic bodies as internal reaction zones. The third group comprises biotite hornblende rocks which form the outer reaction zones of the ultramafic lenses and arose from amphibolites or hornblende gneisses and not from the primary ultramafics.